Rumex dentatus Inhibits Cell Proliferation, Arrests Cell Cycle, and Induces Apoptosis in MDA-MB-231 Cells through Suppression of the NF-κB Pathway - Batool, Riffat; Aziz, Ejaz; Tan, Benny K.-H.; Mahmood, Tariq (Frontiers in Pharmacology, 2017)
Background: Rumex dentatus, commonly known as tooth docked, is widely used in traditional system of medicines. Although it is well reported for its biological activities and medicinal value, only a few studies have been carried out to assess its anticancer potential. Purpose: This study seeks to evaluate the anticancer activity of leaf extracts of R. dentatus against breast cancer MDA-MB-231 cell line, a triple negative human breast cancer cell line with invasive properties and to identify the molecular targets underlying its mechanism of action. Methods: Cytotoxicity of plant extracts was determined against breast cancer cells, using the MTT assay. Flow cytometry was performed to analyze the changes in cell cycle and apoptotic effect, if any. Cells were also studied for their wound healing and invasive potential as well as for western blotting of apoptotic genes and NF-κB pathway. Results: The results revealed that methanol (RM) and chloroform (RC) extracts of R. dentatus had the highest inhibition of cell proliferation in a concentration- and time-dependent manner. This inhibitory effect was found to be linked to arrest of cell cycle at the G0/G1 phase, along with induction of apoptosis and accumulation in the sub-G1 phase. Moreover, it was shown that both RM and RC inhibited the proliferation of the malignant cells and induced apoptosis by repressing the activation of nuclear factor-kappaB (NF-κB) and its subsequent transcripts, Bcl-xl, Bcl-2, Cyclin D1, survivin and XIAP. Apoptosis was also confirmed in the cells as suggested by caspase-3 detection. RM and RC also abrogated IκBa phosphorylation in the malignant cells as well as reduced the invasive and migratory capabilities of these cells. Conclusion: Our findings suggest that the methanol and chloroform extracts of R. dentatus may have anti-cancer compounds that are potentially useful in the treatment of human breast cancer.